Porsenasma Athlete Physical Fitness Classification - Agung Mahendra; M. Taheri Akhbar; Puput Sekar Sari; Husni Faritsani (Universitas PGRI Palembang, 2023)
This research was conducted at PGRI Palembang University. The purpose of this study was to determine the classification of physical freshness of sports athletes at PGRI Palembang University. The method in this study is a quantitative descriptive research method. The research sample was 20 students who became sports athletes at PGRI Palembang University, while the data collection technique used a 2.4 km distance running test with the aim of measuring the physical condition of a person's freshness. From the results of data analysis that has been carried out on the data on the physical freshness test results of athletes in the PGRI Palembang University branch, the results of the physical freshness classification of athletes with a good classification of 6 (six) people or 30%, moderately qualified are 6 (six) people or 30%, less qualified are 8 (eight) people or 40%, while for the average score or mean of the physical freshness test results run 2.4 km, which is 13.57 minutes, Based on the average results of these values, it can be concluded that the condition of physical freshness of sports athletes at PGRI Palembang University is in the Medium classification.